Dinamika Strategi Pemasaran Tabungan E-MAS oleh Marketing Officer pada Bank Syariah Indonesia KC Jember Sudirman - Savina Shafa Afkarina; Zahroh Syifaus Tiqlaliyah; Abdur Rakhman Wijaya (YASIN, 2026)
The development of Islamic banking and the increasing use of digital investment services encourage banks to offer investment products that are secure, practical, and compliant with sharia principles. Tabungan E-mas has emerged as one of the innovations in digital gold investment that requires adaptive marketing strategies to reach various segments of society. This study aims to analyze the dynamics of the Tabungan E-mas marketing strategy implemented by marketing officers at Bank Syariah Indonesia (BSI) Jember Sudirman Branch Office. This study used a qualitative approach with a descriptive design. Data were collected through in-depth interviews with marketing officers and related parties involved in marketing the Tabungan E-mas product at BSI Jember Sudirman Branch Office, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the Tabungan E-mas marketing strategy was implemented through the 7P marketing mix approach, which includes product, price, place, promotion, people, process, and physical evidence. Marketing officers play an important role in customer acquisition through direct socialization, Islamic investment education, personal approaches, and the use of digital media. The marketing programs implemented include Kopi Emas, Grebek Pasar, KEPO (Kunjungan Emas Promosi), and Mini Source. The dynamics of the marketing strategy are reflected in the ability of marketing officers to adjust communication methods based on customer characteristics and field conditions. However, the implementation of the strategy still faces obstacles in the form of public perceptions of usury elements, low literacy in digital gold investment, and competition among investment products. This study affirms that the success of Tabungan E-mas marketing is determined not only by product quality but also by the ability of marketing officers to build trust, provide education, and adapt marketing strategies to community needs. The implications of this study provide practical contributions for Islamic banking in designing digital investment marketing strategies that are educational, adaptive, and based on customer trust.